2020
DOI: 10.1016/j.jinorgbio.2020.110997
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolyzed Ce(IV) salts limit sucrose-dependent biofilm formation by Streptococcus mutans

Abstract: Several studies have focused on the antimicrobial effects of cerium oxide nanoparticles (CeO 2-NP) but few have focused on their effects on bacteria under initial biofilm formation conditions. Streptococcus mutans is a prolific biofilm former contributing to dental caries in the presence of fermentable carbohydrates and is a recognized target for therapeutic intervention. CeO 2-NP derived solely from Ce(IV) salt hydrolysis were found to reduce adherent bacteria by approximately 40% while commercial dispersions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 31 publications
0
10
1
Order By: Relevance
“…Streptococcus mutans forms biofilms that contribute to dental caries in the presence of fermentable carbohydrates and constitutes a target for therapeutic intervention. Ceria NPs reduced bacterial adhesion by 40%, and planktonic growth and dispersal assays supported a non-bactericidal mode of biofilm inhibition [ 188 ]. A detailed study of the bio–nano interface demonstrated that rod-like ceria NPs could be reduced by Bacillus subtilis under planktonic conditions, so that the Ce (III) ions adjacent to the surface oxygen vacancies would be chelated by the adsorption sites present on the bacterial cell wall.…”
Section: (Bio)applicationsmentioning
confidence: 99%
“…Streptococcus mutans forms biofilms that contribute to dental caries in the presence of fermentable carbohydrates and constitutes a target for therapeutic intervention. Ceria NPs reduced bacterial adhesion by 40%, and planktonic growth and dispersal assays supported a non-bactericidal mode of biofilm inhibition [ 188 ]. A detailed study of the bio–nano interface demonstrated that rod-like ceria NPs could be reduced by Bacillus subtilis under planktonic conditions, so that the Ce (III) ions adjacent to the surface oxygen vacancies would be chelated by the adsorption sites present on the bacterial cell wall.…”
Section: (Bio)applicationsmentioning
confidence: 99%
“…, nanoceria, CeO 2 -NP, 3–5 nm) prepared from the in situ hydrolysis of ceric nitrate limited in vitro biofilm adherence of S. mutans with limited toxicity to either human or bacterial cells at moderate concentrations . We continued to investigate these nanoceria as potential oral antibiofilm agents due to their potential for reduced harmful effects on the microbiota.…”
Section: Introductionmentioning
confidence: 99%
“…However, nanoparticles often cannot endure rigorous surface treatments to recondition surfaces after eventual biofilm formation and/or fouling. Metal salts (e.g., Ce(IV)) have been shown to disrupt saccharide-dependent biofilm formation during the kinetically controlled reversible adhesion of primary colonization ( Bhatt et al., 2020 ). However, metal salts often do not persist long term in aqueous environments thereby rendering them inactive.…”
Section: Introductionmentioning
confidence: 99%